SISTEM PENDUKUNG KEPUTUSAN PENANGANAN GIZI BALITA DENGAN METODE FUZZY MAMDANI - Heru Budi Kusumo; Dwi Remawati; Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2018)
Decision Support System is a branch of artificial intelligence used to help make decisions in semi-structured cases, where it is not known exactly how decisions should be made. In this research, the design and making of decision support system that is used to help determine the nutritional status of children with weight input, age, height, head circumference, nutrition value of toddlers and the output of nutritional status of children under five and their handling. The problem of data uncertainty in decision support system is solved by using fuzzy mamdani method. The existence of data uncertainty in the process can occur because of the differences in existing calculations on the system. The process of determining the nutritional status of this decision support system is begun by entering the input data of toddlers, where the system will display some variables that have been made then start the calculation with the application. The end result of this research is decision support system to do nutritional handling in toddler along with their nutrition result. The calculations show the level of confidence in the system of nutritional status of the toddler and from the results of this study obtained the system accuracy of 83.33% of the 18 test data that has been tested is obtained. Therefore, it can be concluded that decision support system produces a good examination.